Avaliação "in vitro" da adição fracionada da dimetilformamida na criopreservação de sêmen equino - Fernanda Guimaraes Cardoso de Mello (2005)
The aim of this research was to evaluate the efficacy of the manner of the cryoprotectantaddition, one or multiple steps, and the cooling rate, on equine semen cryopreservation. Thelesion intensity of the spermatozoa, during the process of the cryopreservation, was also studied.One ejaculate of nine stallions was used to test the modified INRA 82 with 5% of dimetylformamide with the following treatments: addition of the dimethyl formamide in one step andfast cooling rate (T1- control), addition of the dimethyl formamide in multiple steps and fastcooling rate (T2), addition of the dimethyl formamide in one step and slow cooling rate (T3),addition of the dimethyl formamide in multiple steps and slow cooling rate (T4). Aftercentrifugation of ejaculates in INRA 82 extender, sperm pellets were diluted with finalextenders to reach the concentration of 100X106 sperm cells per ml. Semen was frozen threecentimeters above the nitrogen level, during ten minutes, in 0.5 ml straws. Thawing of sampleswas done at 52°C for ten seconds followed by immersion of the straw in a water bath at 37°Cfor thirty seconds. Immediately pos dimethyl formamide addition, total and progressive motilityand sperm vigor were evaluated under light microscope (400X). The functional spermmembrane integrity was evaluated by the hypoosmotic swelling test. No differences betweentreatments were observed, before the cooling of the straw. Immediately post thaw, total andprogressive motility and sperm vigor were evaluated under light microscope (400X). Functionaland structural sperm membrane integrity were evaluated by the hypoosmotic swelling test andfluorescent dyes, carboxyfluorescein diacetate and propidium iodide, respectively. Thespermatozoa was also evaluated in the temperature resistance test. The multiple steps addition ofthe cryoprotectants was better than the one step addition in all parameters valued, independentlyfrom the cooling rate. The slow cooling rate was better than the fast cooling rate in allparameters valued, independently from the manner of the dimethyl formamide addition. It maybe concluded that the association of the multiple steps addition of the dimethyl formamide withthe slow cooling rate is the best protocol to freeze the equine semen and that the lesions causedby osmotic and cold stress may occur during the cooling and freezing process